ОСОБЛИВОСТІ ПЕРЕБІГУ ГНІЙНО- НЕКРОТИЧНИХ ПРОЦЕСІВ ПАЛЬЦЯ У КОРІВ В ЗАЛЕЖНОСТІ ВІД УМОВ УТРИМАННЯ (World Science, 2020)
Among other etiological factors housing conditions have ability to affect the severity of the course of purulent-necrotic processes of the finger in cows. Timely diagnosis of septic inflammatory processes of the finger providing qualified assistance in the early stages of the disease in the barn farms. Under these conditions, the course of purulent-necrotic processes was accompanied by less pronounced clinical symptoms (slight swelling, soreness when pressed on the hoof, pulsation of the finger arteries, increase in local temperature, discharges from a wound and a slight increase in overall body temperature, decrease in milk yields within 10-15%).Diagnosis of disease in the process of progression, namely: permanent maceration of the distal extremity, lameness from moderate to severe, untimely orthopedic treatments and removal of manure is the consequences of loose-housing barn. Cows lost productivity within 15-20%.